From ear modeling to auditory transform - P. KLECZKOWSKI (Archives of Acoustics, 2014)
Understanding how the auditory system works recently gains increasing importance in audio engineering. Its most widespread practical use is in perceptual audio coders, with even more applications to be foreseen in the future. The construction of a mathematical procedure that could transform acoustic signals heard by humans to data corresponding to auditory sensation would open way to significant progress in audio engineering. In this paper the issue is discussed and important research in the field is reviewed. The proposal for a frequency analysis procedure appropriate for ear modeling is presented and verified. This procedure is a form of the Wavelet Transform.